Estudio de las representaciones sociales de autoridades de instituciones educativas y líderes barriales del barrio La Tola sobre participación juvenil - López Díaz, Mónica Paola (2015)
This work shows that the social conceiving about youth participation by the education authorities and the local leadership are based on artistic, cultural, social and emotional activities that the people from “La Tola” have barely experienced. This reality has been fed on limited information from national statistics that show a unfavorable level of poverty, inequity and exclusion, that unavoidably will place youth in a constant state of vulnerability. These social representations will be described as a result of the imperative system that answers to a social structure where participative processes are built only from institutions and local leaderships whose view is compromised, following their own and wishes, limiting the heterogeneity that new generations can bring. In spite of that fact, it is necessary to establish that long term constructions depend on the junction of many factors to be taken in to consideration in this research. By the end of this research we found out a transversal axis which is the generational comparisons that are present in all aspects of everyday life in the community. That is why it is crucial that convergence points can be established in order to design youth proposals from their potential and strength, focused on reinforcing local union and all their actors that can play an important role on youth development so a real participation can be achieved a constant and willing way.